Competitiveness and knowledge-based economy: information and communication technology impact evaluation - Gerasymchuk, Vasyl H.; Sakalosh, Taras V. (Business: Theory and Practice, 2007)
The article reveals economy competitiveness and knowledge-based economy questions and the basis of information and communication technologies influence on this. Methods and competitiveness estimation are presented. The work contains the methods of competitiveness estimation; researching of competitiveness level, human development index, science linkage index of GDP in Ukraine and the stage of high technology development. The authors evaluate the information and communication technologies influence on knowledge-based economy and country’s common wealth.